2016
DOI: 10.2340/00015555-2357
|View full text |Cite
|
Sign up to set email alerts
|

Skin Patterns Associated with Upper Airway Infantile Haemangiomas: A Retrospective Multicentre Study

Abstract: The aim of this study was to define the skin patterns at high risk for upper airway infantile haemangioma. A retrospective multicentre French observational study was conducted between January 2006 and January 2015 and all confirmed airway haemangioma were included. Thirty-eight patients with airway haemangioma from 9 centres were included. Thirty-one patients had a cutaneous or mucosal haemangioma: 21 with a location considered at high risk for airway haemangioma (large segmental mandibular haemangioma), 4 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…9,[11][12][13] IHs with life-threatening complications include obstructive airway hemangiomas such as subglottic hemangiomas (Fig. 1), [35][36][37][38] hepatic IHs associated with high-output congestive heart failure and hypothyroidism, 39,40) and profuse bleeding from ulcerated IHs. 11) Subglottic hemangiomas are diagnosed at mean age of 4 months, and patients present with progressive biphasic stridor, a barking cough, and dyspnea, and they may be misdiagnosed with congenital laryngeal stridor or infectious croup.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…9,[11][12][13] IHs with life-threatening complications include obstructive airway hemangiomas such as subglottic hemangiomas (Fig. 1), [35][36][37][38] hepatic IHs associated with high-output congestive heart failure and hypothyroidism, 39,40) and profuse bleeding from ulcerated IHs. 11) Subglottic hemangiomas are diagnosed at mean age of 4 months, and patients present with progressive biphasic stridor, a barking cough, and dyspnea, and they may be misdiagnosed with congenital laryngeal stridor or infectious croup.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%
“…Airway IHs cause functional damage due to upper airway obstruction leading to respiratory insufficiency and life-threatening complications in the absence of treatment. They are frequently associated with a cutaneous distribution in a known fashion ( 3 ). Although, as seen in our case series and in the literature, they can present without cutaneous involvement.…”
Section: Discussionmentioning
confidence: 99%
“…However, they can also develop in children in the absence of cutaneous hemangiomas. Moreover, recent studies demonstrated that AIHs might be associated with more limited skin patterns, as well as with posterior and lateral neck involvement ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Segmental IH located in the beard area often involves the pharynx and larynx, thus greatly increasing the risk of airway obstruction. 3,21 As a high-risk type of IH, segmental IH has a high possibility of inducing structural abnormalities, such as PHACE syndrome and LUMBAR syndrome. 4,8,22 In addition, segmental IH may be associated with a higher risk of concomitant hepatic hemangioma than nonsegmental IH.…”
Section: Discussionmentioning
confidence: 99%